Aconitum anhuiense sp. nov. (Ranunculaceae), a new species from Anhui, China. (21st November 2021) - Yin, Min‐Zhen; Peng, Hua‐Sheng; Huang, Lu‐Qi
Abstract : Aconitum anhuiense, a new species from Anhui Province, China, is described and illustrated. The species is similar to A. hemsleyanum and A. henryi, but can be distinguished by a suit of unique traits such as leaf blade abaxially sparsely puberulent at veins and 3‐parted to 2–4 cm from base, spur circinate, lip shorter, carpels 3 and seeds longer. Detailed information, including morphological descriptions, illustrations and diagnostic comparisons of the new species are provided.